EDUCATIONAL STRATEGIES FOR CERVICAL CANCER PREVENTION IN YOUNG PEOPLE: DEVELOPING A CONSCIOUS ATTITUDE TOWARDS WOMEN'S HEALTH (World Bulletin of Public Health, 2025)
This article assesses young people's awareness of the human papillomavirus (HPV), prevention methods, and vaccination against it, as well as identifies barriers to vaccination. The study is based on a survey of girls aged 16–25 in Tashkent. The findings indicate fragmented knowledge and insufficient vaccination coverage, despite government efforts. Social, educational, and cultural factors influencing attitudes toward HPV and vaccination are discussed, and strategies for increasing youth awareness and prevention coverage are proposed.
Keywords: Human papillomavirus; vaccination; awareness; prevention